Corruption and female regional heads in Indonesia according to feminist legal theory - Fadila Nur Annisa; Rosa Ristawati; Ana Fauzia (Komisi Pemberantasan Korupsi, 2024)
Corruption cases by regional heads nowadays do not only affect men but also women. This is evidenced by several cases that occurred in female regional heads. Normatively, regulations related to women's rights have been well accommodated, especially regarding their rights to run for regional heads. Therefore, the concept of feminism that is applied is no longer related to the struggle for women's rights, but to ensure the quality of women's leadership in accordance with the goals of feminism. The concept of the study carried out was raised by basing it on the concepts of lberal based, anti-essential model, and post-modern liberalism. These three concepts are studied based on the varieties of motives and accessibility of women's potential to commit corruption when they become regional heads. After that, this article discusses at a practical level the leadership of women in the regions involved in corruption. By basing on court decisions dealing with corruption of regional heads by women, this article analyzes the factors of accessibility, impulsive buying, women's powerlessness, and gender bias in sentencing. The results of this study show that in some cases, there are factors that indeed female regional heads commit corruption based on personal motives, but there are also those based on the context of powerlessness to regulatory factors that make women feel they are given “special” rights in the judicial process.